Analysis Of Factors Affecting Corporate Values With Dividend Policy As Intervening Variables In The Property And Real Estate Companies Listed In Indonesia Stock Exchange Period 2014-2018: Analysis Of Factors Affecting Corporate Values With Dividend Policy As Intervening Variables In The Property And Real Estate Companies Listed In Indonesia Stock Exchange Period 2014-2018 - Devi Ridhani; Idhar Yahya; Murni Daulay (Institute of Computer Science (IOCS), 2020)
This study aims to determine and analyze the factors that influence the value of the company, namely debt policy, profitability, goodwill and free cash flow with dividend policy as an intervening variable in property and real estate companies listed on the Indonesia Stock Exchange period 2014-2018. The population in this study amounted to 54 companies. The sample selection method uses a purposive sampling technique, so the number of samples used is 9 companies. The data analysis method uses multiple linear regression analysis and path analysis using the Eviews software tool. The first test results show that in alpha five percent of debt policy and free cash flow have a significant positive effect on firm value, goodwill has no significant negative effect on firm value. Profitability and dividend policy have a significant positive effect on company value. The second test results show that debt policy, goodwill and free cash flow have a significant positive effect on dividend policy, while profitability has a significant positive effect on dividend policy. The third test result is that dividend policy is only able to mediate goodwill and free cash flow to the value of the company. But the dividend policy is not able to mediate debt and profitability policies to the value of the company.